ANALISIS PERAN PEMANGKU KEPENTINGAN PADA PENERAPAN TATA KELOLA KORPORAT USAHA MIKRO KECIL DAN MENENGAH KOTA SURABAYA - Nugraheni, Bernadetta Diana; Martono, Cyrillius (Jurnal Akuntansi Kontemporer, 2019)
In general, the implementation of MSMEs has not implemented good organizational governance, especially in the principles of transparency and accountability. This study aims to examine and analyze the roles and responsibilities of stakeholders, especially the owners and managers of MSMEs in implementing organizational governance, in the city of Surabaya. This research is an exploratory study with survey design. Population and sample of this study took UMKM in the city of Surabaya. The results of this study can be concluded that the principle of transparency as a whole has not been realized properly. On the principle of accountability related to responsibility in compiling reports on organizational activities and the implementation of monitoring and evaluation of the work of employees can be said to be quite good. While the principle of responsibility as a whole is said not to materialize. On the principle of independence, the authority to coordinate daily operational tasks does not materialize. And on the principle of reasonableness indicates that there are still management interventions from the owner / family